Determinants of Intentions to Engage in Sustainability Accounting & Reporting (SAR) and Moderating Role of Internal Audit Function: The Perspective of Accountants - Ooi Chee Keong (Arthatama: Journal of Business Management and Accounting, 2020)
The purpose of this paper is to identify the determinants of engaging in sustainability accounting and reporting (SAR) and their impact on SAR. This paper also analyses the moderating role of internal audit function on engaging in SAR from the perspective of accountants. The paper has adopted quantitative design in which, data was collected from 315 accountants using survey questionnaire. The data is analysed using PLS-SEM technique along with CFA. The results revealed that only perceived behavioural control has a significant effect on intention to engage in SAR while internal audit function significantly moderates the relationship of perceived behavioural control and subjective norms with intention to engage in SAR. The study is useful for accountants and firms that intend to engage in SAR. The study is limited to perception of accountants and has only considered quantitative data.